Solar Neutrino Physics: Sensitivity to Light Dark Matter Particles - Lopes, I (2012)
Neutrinos are produced in several neutrino nuclear reactions of the proton-proton chain and carbon-nitrogen-oxygen cycle that take place at different radii of the Sun's core. Hence, measurements of solar neutrino fluxes provide a precise determination of the local temperature. The accumulation of non-annihilating light dark matter particles (with masses between 5 GeV and 16 GeV) in the Sun produces a change in the local solar structure, namely, a decrease in the central temperature of a few percent. This variation depends on the properties of the dark matter particles, such as the mass of the particle and its spin-independent scattering cross-section on baryon-nuclei, specifically, the scattering with helium, oxygen, and nitrogen among other heavy elements. This temperature effect can be measured in almost all solar neutrino fluxes. In particular, by comparing the neutrino fluxes generated by stellar models with current observations, namely 8B neutrino fluxes, we find that non-annihilating dark matter particles with a mass smaller than 10 GeV and a spin-independent scattering cross-section with heavy baryon-nuclei larger than 3 × 10-37 cm-2 produce a variation in the 8B neutrino fluxes that would be in conflict with current measurements.